2009
DOI: 10.1362/026725709x429791
|View full text |Cite
|
Sign up to set email alerts
|

Methodological reasons for the theory/practice divide in market segmentation

Abstract: A theory/practice divide exists in market segmentation. The main reasons are the focus of academic studies on statistical techniques, and managers' lack of understanding of fundamental segmentation basics (Dibb 2005;Greenberg and McDonald 1989). To date, only one study has explored methodological reasons for the theory/practice divide: Dibb and Simkin 1994. We extend their work by: (1) detailing key methodological aspects likely to cause difficulties in translating segmentation findings into managerially usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 33 publications
4
43
0
1
Order By: Relevance
“…Vremenom, sa razvojem novih koncepata i tehnika marketinga "1 na 1", ali i usled neadekvatne primene segmentacije i problema povezanih sa njenom praktičnom implementacijom, sve više naučnika i struč-njaka ima kritički pristup, a pojedini autori misle da je u velikoj meri prevaziđena (Dolnicar & Lazarevski, 2009) . Opet, višestruke prednosti su evidentne, pa se često i ne razmatra da li je potrebna segmentacija ili ne, već konkurencija i heterogene potrebe potrošača same nameću njenu neophodnost .…”
Section: Prednosti Segmentacije Tržištaunclassified
“…Vremenom, sa razvojem novih koncepata i tehnika marketinga "1 na 1", ali i usled neadekvatne primene segmentacije i problema povezanih sa njenom praktičnom implementacijom, sve više naučnika i struč-njaka ima kritički pristup, a pojedini autori misle da je u velikoj meri prevaziđena (Dolnicar & Lazarevski, 2009) . Opet, višestruke prednosti su evidentne, pa se često i ne razmatra da li je potrebna segmentacija ili ne, već konkurencija i heterogene potrebe potrošača same nameću njenu neophodnost .…”
Section: Prednosti Segmentacije Tržištaunclassified
“…Yet, very little practical guidance is available to help users to choose the best segmentation solution. This lack of guidance is particularly concerning because (1) the sample and the algorithm used introduce a significant amount of randomness into the final segmentation solution, (2) no clear distinction is currently made between solutions that reveal naturally existing clusters (density clusters) and solutions that construct clusters, and (3) managers have significant knowledge gaps in relation to segmentation methodology and cannot be expected to make an informed decision about the final market segmentation solution that should be used as a basis for strategic decisions (Dolnicar and Lazarevski, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…. often meaningless information • In a PowerPoint presentation with a slick handout (quotes from the study reported in Dolnicar and Lazarevski 2009).…”
mentioning
confidence: 99%